Comparison of the capacity of biological desulfurization of Thiobacillus ferrooxidans from different sulfur-containing substrates with or without additional ferrous iron - Wang, Yanjin; Chang, Xiaopeng; Tao, Hongge; Wang, Zhenfeng; Zhang, Quanguo (International Journal of Agricultural and Biological Engineering, 2024)
Thiobacillus ferrooxidans, abbreviated as T. ferrooxidans is one of the important microorganisms in the field of biological desulfurization. Effects of ferrous iron and sulfur-containing substrates on biological desulfurization of T. ferrooxidans were studied. Results show that in the absence of Fe2+, T. ferrooxidans can utilize three kinds of sulfur-containing substrates of Na2S2O3, elemental S and Na2SO3 for growth and metabolism. For utilization complexity, Na2S2O3 was easiest to use, next was elemental S, and Na2SO3 was the worst for use. During the utilization of ferrous iron and sulfur-containing substrates by T. ferrooxidans, the iron oxidation system was first started. With the decrease of the Fe2+ concentration, the sulfur oxidation system was started, and then the two systems synergistically acted. The presence of three sulfur-containing substrates had different effects on Fe2+ oxidation, and elemental S did not inhibit the oxidation of Fe2+, while Na2S2O3 and Na2SO3 had some inhibition on the oxidation of Fe2+, especially the inhibition of Na2SO3 was significant, and complete oxidation of ferrous iron needed more time. The isolated T. ferrooxidans is applied to the removal of H2S gas, aiming to provide a new technological approach for biological removal of H2S. Keywords: Thiobacillus ferrooxidans, ferrous iron, sulfur-containing substrate, biological desulfurizationDOI: 10.25165/j.ijabe.20241703.8613Citation: Wang Y J, Chang X P, Tao H G, Wang Z F, Zhang Q G. Comparison of the capacity of biological desulfurization of Thiobacillus ferrooxidans from different sulfur-containing substrates with or without additional ferrous iron. Int J Agric & Biol Eng, 2024; 17(3): 140-143.